The Influence of Sowing Dates and Schemes on the Formation of Yield Attributes of Chickpea Varieties in the Rainfed Area of the Southern Region of Uzbekistan - Abdiyev, A. A.; Tursunova, M. K. (American Journal of Botany and Bioengineering, 2025)
Chickpea is an important source of protein for millions of people in the developing countries, particularly in South Asia, who are largely vegetarian either by choice or because of economic reasons. Seed is the main edible part of the plant and is a rich source of protein, carbohydrates and minerals especially for the vegetarian population. The current study aimed to investigate the effects of chickpea sowing dates and schemes on yield attributes of chickpea. The objects of study were the local chickpea varieties such as "Obod", "Malhotra" and "Jahongir". In the conditions of rainfed area, the highest yield elements of chickpea varieties were recorded in the February 1st sowing date, especially in the 60×12-1 planting system.